Smrt v lidových představách obyvatel kyperské horské vesnice: (Obec Peristerona, JZ část Kypru) - Jeřábková, Petra (Lidé města, 2003)
The death is very dosely connected with everyday life of the local community of Cyprus village called Peristerona. Members of the village community believe in after-life. That is why they are afraid of harmful and dangerous behaviour of the dead man not only immediately after his passing but also for certain period of time after the burial. They believe that a dead man starts his journey to the netherworld, to the place of his last rest. According the folk imaginations of the members of the village community the soul does not leave the body in the moment of passing, but remains inside the body until the journey of the dead man to the netherworld is not completed. Because of the belief in the union of the body .ind the soul it is obligatory to provide the deact man with material equipment. However the inhabitants of the Peristerona village have no detailed and developed imagination of the after-life and the place of the last rest of dead people. lt is obvious that elements of the antic tradition remained in the folk beliefs of the village community - especially the fact that the dead man goes to netherworld but not to paradise ar hell as it is known in the Christian tradition. The natural way of dying is understood as a gradual leaving, gradual and very slow cutting off the links with the family, neighbours and all members of the village community. This slow leaving is happening in three phases: passing, passage period (here belongs the guarding of the dead man, preparation for the last journey and the funeral itself) and the completion of the journey to the netherworld.